On Quasi Quadratic Modules of Lie Algebras - Ummahan Ege Arslan; Emre Özel (Journal of New Theory)
This study introduces the category of quasi-quadratic modules of Lie algebras and discusses the functorial relations between quasi-quadratic modules and quadratic modules of Lie algebras.